A Case Study on Pre-Service Teachers’ Implementation of Bilingual Teaching Strategies in Elementary Education - T. M. S. B, Siregar; Siwabessy, Najwa Naraya; Pandiangan, Irene Angelina; Nazla, Khalisa; Aritonang, Angel (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
In the context of increasingly globalized education and diverse learning resources, bilingual teaching strategies have gained attention as a way to support effective English instruction in elementary schools. This qualitative case study investigates how pre-service primary school teachers (PGSD students) apply bilingual strategies particularly translanguaging and code-switching during teaching practices. Data were collected through a systematic literature review (2020–2025) and semi-structured interviews with pre-service teachers. The literature shows that translanguaging and code-switching help improve comprehension, classroom engagement, and learner confidence. Interview data confirms that pre-service teachers intentionally use bilingual strategies to make learning more accessible and supportive. However, challenges such as limited bilingual teaching materials and student discomfort with English were reported. The study concludes that bilingual strategies, when applied thoughtfully and contextually, can contribute positively to English teaching in elementary settings; therefore, teacher education programs should include structured training on bilingual pedagogy.